Rancang Bangun Mesin Penebar Pakan Ikan Berbasis Programmable Logic Controller - Sukma Ardiyan; Diky F; Winarto Winarto; Ridwan Baharta (Jurnal Ilmiah Teknik Pertanian - TekTan, 2020)
The fish feed spreader machine is a feeding tool that is made to facilitate fish breeders in feeding fish. The fish feed spreader is specially programmed to provide fish feed according to the schedule and the desired dose. The purpose of making this tool is to design a fish feed spreader machine based on the logic controller programmale, and to test the performance of the designed fish feed spreader machine. The results showed that the average feed expenditure was 2.66 kg for a duration of 40 seconds. Then for the farthest throw of feed is 7.5 meters, while for throw of feed that is evenly distributed it has a distance of 5 meters with a spread width of 5.85 meters, and the angle of spread of feed is 90º.